KARAKTERISTIK PERAWAT YANG MEMPENGARUHI PERILAKU CARING DI RS PKU MUHAMMADIYAH TEMANGGUNG - Luthfi Fauzi Asriyanto; Puguh Widiyanto; Sodik Kamal (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2015)
Quality health care becomes an absolute must for a health care institution, as a special effect to the image, profits, productivity, and liability. One of the keys of the quality of health services provided by a nurse lies in aspects of attention, empathy, and caring. Based on preliminary studies in PKU Muhammadiyah Hospital Temanggung, it can be concluded that the nurse caring behavior can’t be said to be optimal, although the management of the hospital has established a commitment to quality service through its quality policy.This study aims to determine the factors fatherly dimensions of personal characteristic that influence nurses caring behavior. The study design used was a cross sectional analytic method in 50 nurses. Data analysis using Pearson and Spearman correlation test, with the result there is no relationship between gender and marital status with nurses caring behavior, whereas age and years of nursing has a significant relationship. Multivariate analysis showed that the variables that most influence the caring behavior is working lives, so suggestions for management of the hospital to take care of inserting items into the standard of care and nursing performance appraisal.